Uncle Drew [videorecording (DVD)] - Irving, Kyrie, 1992-; Howery, LilRel; Webber, Chris, 1973-; O'Neal, Shaquille (Summit Entertainment, 2018)
After draining his life savings to enter a team in the Rucker Classic street ball tournament in Harlem, Dax is dealt a series of unfortunate setbacks, including losing his team to his longtime rival. Desperate to win the tournament and the cash prize, Dax stumbles upon the man, the myth, the legend Uncle Drew and convinces him to return to the court one more time.